2018
DOI: 10.1016/j.cbpa.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Proteins, air and water: reporter genes for ultrasound and magnetic resonance imaging

Abstract: A long-standing goal of molecular imaging is to visualize cellular function within the context of living animals, necessitating the development of reporter genes compatible with deeply penetrant imaging modalities such as ultrasound and magnetic resonance imaging (MRI). Until recently, no reporter genes for ultrasound were available, and most genetically encoded reporters for MRI were limited by metal availability or relatively low sensitivity. Here we review how these limitations are being addressed by recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…The acoustic impedance mismatch occurring between the gas interior of GVs with surrounding aqueous media makes the GVs to strongly scatter sound waves, a prerequisite for using them as ultrasound (US) contrast agents as their initial imaging application [ 255 , 442 , 443 , 444 , 445 ]. These GVs generate robust US contrast across a range of frequencies at pM concentrations and also exhibit harmonic scattering that enable enhanced detection without any background in vivo [ 255 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic impedance mismatch occurring between the gas interior of GVs with surrounding aqueous media makes the GVs to strongly scatter sound waves, a prerequisite for using them as ultrasound (US) contrast agents as their initial imaging application [ 255 , 442 , 443 , 444 , 445 ]. These GVs generate robust US contrast across a range of frequencies at pM concentrations and also exhibit harmonic scattering that enable enhanced detection without any background in vivo [ 255 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…Interestingly, the MR contrast generated by susceptibility measurements of GVs can be modulated using ultrasound (US) in order to avoid background interference. Additionally, the acoustic properties of GVs were utilized in 1 H MRI where the serial acoustic collapse of GVs engineered with certain collapse thresholds were performed to achieve multiplexed imaging [ 445 ]. This option could also be included in Xe MRI detection protocols.…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…Moreover, in vivo bacterial imaging by detecting bioluminescence often had unsatisfactory spatial resolution . Bacteria engineered with acoustic reporter proteins, which could form hollow nanostructures inside bacteria and respond to ultrasound detection, exhibited improved spatial resolution and suitability to anaerobic environment . Notwithstanding these advantages, the use of this method, like other genetic engineering strategies, is limited to genetically modifiable bacteria, which currently account for only a very small proportion of intestinal bacteria.…”
Section: Figurementioning
confidence: 99%
“…Inspired by gas-vesicle-forming photosynthetic microbes, which produce these vesicles to control the organisms' buoyancy, Shapiro et al characterized these gas vesicles that also contain iron and showed that they are active as US and MRI contrast agents [94][95][96]. The genetic precursors of these complex protein vesicles were then determined and used as a US and MRI gene reporter system [96]. The extremely high sensitivity of US should prove to be a powerful tool to label and track SCs.…”
Section: Ultrasoundmentioning
confidence: 99%